2019
DOI: 10.1021/acs.inorgchem.8b03031
|View full text |Cite
|
Sign up to set email alerts
|

Palladium–Schiff Base Complexes Encapsulated in Zeolite-Y Host: Functionality Controlled by the Structure of a Guest Complex

Abstract: A series of palladium complexes of tetradendate Schiff base ligands L1 (N,N′-bis(salicylidene)phenylene-1,3-diamine) and its derivatives L2 and L3 have been synthesized by using the "flexible ligand method" within the supercage of zeolite-Y. These complexes in both their free and encapsulated states have been thoroughly characterized with the help of different characterization tools such as XRD, SEM-EDS, BET, thermal analysis, XPS, IR, and UV−vis spectroscopic studies. All these encapsulated complexes are iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…IR spectrum of H 2 L exhibited a strong absorption band at 1616 cm -1 (C=N) (Table 2) [19]. In the spectrum of Tb_L complex the ν(C=N) absorption band was redshifted to 1602 cm -1 [18,19] due to the fact that Tb(III) ion could act as a Lewis acid, pulling away the electron density at the C=N group (Lewis base) due to coordination which weakened the C=N double bond character. Phenol 2) [18,22,33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IR spectrum of H 2 L exhibited a strong absorption band at 1616 cm -1 (C=N) (Table 2) [19]. In the spectrum of Tb_L complex the ν(C=N) absorption band was redshifted to 1602 cm -1 [18,19] due to the fact that Tb(III) ion could act as a Lewis acid, pulling away the electron density at the C=N group (Lewis base) due to coordination which weakened the C=N double bond character. Phenol 2) [18,22,33].…”
Section: Resultsmentioning
confidence: 99%
“…S. Dalapati and co-authors [15] demonstrated that H 2 L ligand can act as a colorimetric receptor selectively detecting AcOand Fions by UV-Vis spectral changes as well as by naked eye colour change (colourless to yellow). Several groups reported synthesis and characterization of H 2 L ligand and its transition metal complexes {Ni(II), Co(II), Co(III), Cu(II), and Zn(II)}, [16][17][18][19][20][21]. Supported by spectral techniques, such as UV-Vis, FT-IR, and NMR spectra, X-ray crystallography, elemental and molar conductivity analysis, H 2 L ligand was characterised as a tetradentate N 2 O 2 type bounding to metal atoms through oxygen and nitrogen atoms of the hydroxyl and imine groups, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…2a). 24 In addition, in contrast to the weak fluorescence in good solvent conditions (acetonitrile), the complex DZ1 exhibited strong fluorescence in ethyl acetate (poor solvent), which attracted our attention. We envisioned that DZ1 had AIE in ethyl acetate/acetonitrile mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…However, the catalytic mechanism for the Pd-SALOPHEN catalysts could involve the formation of intermediates Pd(II)-Pd(0) [67,68], or different reaction states based on the participation of Pd(II)-Pd(IV) intermediates [69,70]. Recently, Venkateswarlu et al proposed a modified mechanism for the Heck reaction, which involves the use of a Pd(II)-porphyrin tetradentate N 4 complex [71], as shown in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of PdAS(1)-MA and PdAS(2)-MA, lower activities were observed for these catalysts compared with Pd-SALOPHEN due to the steric constraints provided by the resin influencing the geometry of the Pd-SALOPHEN complex, and consequently modifying the catalyst’s electronic and redox properties [67]. TEM characterization was then carried out on the used PdAS(1)-MA and PdAS(2)-MA catalysts, as shown in Figure 8c,d.…”
Section: Resultsmentioning
confidence: 99%